The Maker Faire of Rome as a window of observation on the new perspectives for local economic development and the new urban entrepreneurial ecosystems. (June 2019) - Fiorentino, Stefania
The rise of the Maker Movement – representing small businesses active in the digital fabrication and the creative industry field – is indicative of the emergence of a new type of urban economy and labour regulations in many cities. Trade fairs have been central to the dynamics of these makers as well as an institutional tool to build an economic reputation for the place hosting them. This paper draws upon a survey of exhibitors at, and interviews with organizers of, the Maker Faire of Rome 2015 to describe the features of this unfolding entrepreneurial world. The findings indicate that, although cities are once again the nexus of contemporary innovation trends, these are deeply intertwined with the surrounding socio-political context. Specifically, and in some contrast to the extant literature on creativity, the Rome case indicates the salience of Makers to those urban economies most in need of regeneration.